1988
DOI: 10.1161/01.str.19.9.1156
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis and pure motor hemiparesis.

Abstract: A 49-year-old man with meningeal cysticercosis presented with a pure motor hemiparesis. Computed tomography and magnetic resonance imaging showed a capsular infarction and a suprasellar cyst with surrounding arachnoiditis. Cerebrospinal fluid analysis confirmed the diagnosis as it showed positive immunologic reactions to cysticerci. This is the first reported case of pure motor hemiparesis due to a parasitic disease of the central nervous system. (Stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The most frequent are lacunar infarctions in the anterior or middle cerebral artery territory, resulting from occlusive endarteritis secondary to the inflammatory reaction within the subarachnoid space [60][61][62]. Large infarcts involving deep and superficial sites of a major intracranial artery have occasionally been reported [36,[63][64][65].…”
Section: Vascular Eventsmentioning
confidence: 99%
“…The most frequent are lacunar infarctions in the anterior or middle cerebral artery territory, resulting from occlusive endarteritis secondary to the inflammatory reaction within the subarachnoid space [60][61][62]. Large infarcts involving deep and superficial sites of a major intracranial artery have occasionally been reported [36,[63][64][65].…”
Section: Vascular Eventsmentioning
confidence: 99%
“…The following stroke syndromes were considered: (1) symptomatic cerebral infarction, defined as a rapidly de¬ veloping focal loss of cerebral function with symptoms last¬ ing more than 24 hours1' that was associated with a cor¬ responding ischemie area on a CT or MRI scan; (2) silent cerebral infarction, defined as an asymptomatic brain le¬ sion of ischemie origin disclosed by neuroimaging stud¬ ies18; and (3) a transient ischemie attack (TIA), defined as an acute focal neurologic deficit that lasted less than 24 hours.,g…”
Section: Groups 1 Andmentioning
confidence: 99%
“…Several reports have found stroke to be most commonly associated with a focal cystic lesion leading to an occlusive arteritis in small perforating vessels, resulting in lacunar infarction. 2,3,7,8 One series found that more diffuse disease with an intense inflammatory reaction is associated with a higher incidence of ischemic events. 9 Arterial thrombosis has been demonstrated by angiographic studies of patients with cerebral cysticercosis.…”
mentioning
confidence: 99%